2012
DOI: 10.1039/c1sc00582k
|View full text |Cite
|
Sign up to set email alerts
|

A thermally stable {FeNO}8complex: properties and biological reactivity of reduced MNO systems

Abstract: Reduced nitrogen oxide ligands such as NO-/HNO or nitroxyl participate in chemistry distinct from nitric oxide (NO). Nitroxyl has been proposed to form at heme centers to generate the Enemark-Feltham designated {FeNO} 8 system. The synthesis of a thermally stable {FeNO} 8 species namely, [Co(Cp*)2][Fe(LN4)(NO)] (3), housed in a heme-like ligand platform has been achieved by reduction of the corresponding {FeNO} 7 complex, [Fe(LN4)(NO)] (1), with decamethylcobaltocene [Co(Cp*)2] in toluene. This complex readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 41 publications
(50 reference statements)
8
81
2
1
Order By: Relevance
“…Coordination of HNO or its anion to Fe has been proposed in several heme and non-heme systems as described previously [31,32,34,35,[41][42][43][44]59]. Although the list is sparse, the collective use of porphyrin and cyclam N-ligands has been a popular choice in the construction of {FeNO} 8 complexes.…”
Section: Synthesis Of {Feno} 7 Complexesmentioning
confidence: 98%
See 2 more Smart Citations
“…Coordination of HNO or its anion to Fe has been proposed in several heme and non-heme systems as described previously [31,32,34,35,[41][42][43][44]59]. Although the list is sparse, the collective use of porphyrin and cyclam N-ligands has been a popular choice in the construction of {FeNO} 8 complexes.…”
Section: Synthesis Of {Feno} 7 Complexesmentioning
confidence: 98%
“…These values were largely in agreement with theoretical calculations for small molecules with diamagnetic ground states. Non-heme examples of {FeNO} 8 are even rarer with a total of three such reported complexes [41,42] to date and only one being isolable [43]. The extensive spectroscopic studies by Wieghardt on [Fe(cyclam-ac)(NO)] represent the first reported non-heme derivative [42].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A series of 5C Fe-nitroxyl heme-complexes have been obtained by reducing the corresponding n ¼ 7 compounds with cobaltocene derivatives in nonaqueous medium (154,161). The diamagnetic TFPBr 8 -compound (Table 3) has been isolated and characterized by UV-vis, FTIR, 1 H, 15 N NMR spectroscopies and DFT calculations and is very stable in CH 2 Cl 2 , in the absence of oxygen (155).…”
Section: No 2 -Complexesmentioning
confidence: 99%
“…This species was obtained by reaction of the corresponding Co(II)-(TPP) with NO, and it is a representative example of a number of well-defined Co(III)-(NO À ) porphyrinate systems, which are all diamagnetic and square-pyramidal (18,53), as is also the recently prepared Co(III)-LN 4 complex with four asymmetrically bound basal N-ligands in a nonmacrocyclic heme platform (161). The Co(III)-tropocoronand (TCC) derivatives show a distinctive behavior: the diamagnetic 4,4-complex shows a bent nitrosyl in the equatorial position of a trigonal bypyramid, while the 3,3-complex is a paramagnetic square-pyramid (153).…”
Section: No 2 -Complexesmentioning
confidence: 99%